(untitled) (World Economics and Finance Bulletin, 2024)
This article presents alternative energy sources and their pros and cons, as well as goals for the transition to renewable energy sources in countries around the world. In addition, a number of measures on the effective use of renewable energy sources in our republic have been highlighted